Estudio quimico de las hojas de tabernaemontana arborea rose - Cabezas Pizarro, Jorge A. (1986)
From the leaves of Tabernaemontana arborea Rose (Apocynaceae) the triterpenoid lupeyl acetate and the indole alkaloids voacangine, 19 epivoacristine, vobasine and 19R-hydroxiconopharingine have been isolated and identified by spectroscopic methods.